2017
DOI: 10.4103/0366-6999.211550
|View full text |Cite
|
Sign up to set email alerts
|

Nine-hole Peg Test and Ten-meter Walk Test for Evaluating Functional Loss in Chinese Charcot-Marie-Tooth Disease

Abstract: Background:The 9-hole peg test (9-HPT) and 10-meter walk test (10-MWT) are commonly used to test finger motor function and walking ability. The aim of this present study was to investigate the efficacy of these tests for evaluating functional loss in Chinese Charcot-Marie-Tooth (CMT) disease.Methods:Thirty-four Chinese CMT patients (CMT group) from August 2015 to December 2016 were evaluated with 9-HPT, 10-MWT, CMT disease examination score, overall neuropathy limitation scale (ONLS), functional disability sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This suggests that the NHPT is a suitable tool to evaluate dexterity and progression in ALS patients. This is in line with previous studies of other diseases with involvement of upper or lower motor neurons that indicate that the NHPT is a suitable tool for patients with a primary involvement of the UMNs and LMNs [6–11]. In our study, we found a significant difference between ALS patients compared with controls using TMS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that the NHPT is a suitable tool to evaluate dexterity and progression in ALS patients. This is in line with previous studies of other diseases with involvement of upper or lower motor neurons that indicate that the NHPT is a suitable tool for patients with a primary involvement of the UMNs and LMNs [6–11]. In our study, we found a significant difference between ALS patients compared with controls using TMS.…”
Section: Discussionsupporting
confidence: 93%
“…Also, both measurements (TMS RMT and NHPT) were not combined before in a study. NHPT duration is a reliable tool that has been used in studies investigating diseases affecting UMNs and LMNs for years [6–11]. In this study, significantly longer NHPT durations were observed in patients compared with controls.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The 10MWT has measured locomotor capacities in adults [5,6] and children [7][8][9][10][11] with several neuromotor diseases. However, the operational procedures can influence the outcome of the 10MWT, as shown in adults [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…MUNIX, EDx, clinical outcome measures, including MRCSS, ONLS, R-ODS, Jamar handgrip dynamometry, timed 10-meter walk test (10MWT), pinch power test, and nine-hole peg test (NHPT), were performed at baseline and after 6 months, according to previously validated and published protocols. [17][18][19] Manual muscle testing was used to measure the muscle strength bilaterally according to the MRCSS (ranging from 0 to 60 points) for shoulder abduction, elbow flexion, wrist extension in upper extremities and hip flexion, knee extension, and ankle dorsiflexion in the lower extremities.…”
Section: Functional Measuresmentioning
confidence: 99%